Peri Cholecystectomy Bile Analysis for Fasciola hepatica Eggs in Sulaimani Teaching Hospital - Hama Shareef, Seerwan; Abdullah Hawramy, Taher; jamal nasrulla, Osman; Hama amin, Karwn; Ahmed Mohammed, Dara; Seerwan Hama, Raz (Kurdistan Journal of Applied Research, 2019)
Fascioliasis is one of the oldest zoonotic infestations, which returned back to 3000 years B.C., it is caused by Fasciola hepatica or gigantica. It is a widespread disease throughout the world; nearly (2.4 – 17) millions of people is infected. Human is an accidental final host by ingestion of contaminated plants and water by metacircaria. Most of patients suffer from right upper abdominal pain with eosinophilia. Diagnosis is made on clinical background with imaging studies or laboratory (like stool and examinations biliary aspirate, intradermal test or ELISA to detect antibody). It must be taken into consideration as newly emerging infestation in our country. The aim of this study is to highlight on the magnitude of Peri Cholecystectomy Bile Analysis for Fasciola hepatica in Sulaimani province, Kurdistan region and even in Iraq as a whole. A prospective study was performed at Sulaimani Teaching Hospital. Bile samples were collected from who had cholecystectomy. Microscopical analysis was archived for finding egg of the parasite. In 129 samples, there were 7 (5.4%) positive cases of Fasciola hepatica 2 were adult worms, all were swimming in the gall bladder. 5 (3.9%) out of 7 (5.4%) samples were females and only 2 (1.5%) of cases were males. 4 (3.1%) out of 7 were from Sharazur terrain, and 3 (2.3%) of them from the center of Sulaimani city. Fascioliasis is a zoonotic problem. It must be put in differential diagnosis of any vague upper abdominal pain. It is a public health issue, so health worker must give awareness to the society about this disease, which is more easily preventable.